A True Aneurysm of the Zygomatic Orbital Artery: First Case Report in the Literature - Valentina Molinaro; Elisa Pagliasso; Gianfranco Varetto; Claudio Castagno; Lorenzo Gibello; Pietro Rispoli (Case Reports in Medicine)
A 33-year-old man presented with a pulsatile mass in the left temporal region; about 1 year before the current presentation, the swelling had arisen on the upper lateral border of the orbital arch and increased in recent months. His medical history was negative for accidental or iatrogenic head injury. Color echo Doppler and angio-computed tomography demonstrated a fusiform aneurysm of the zygomatic orbital artery, a branch of the superficial temporal artery. Blood tests were negative for human immunodeficiency virus (HIV), hepatitis C (HCV), and hepatitis B (HBV) markers. Aneurysmectomy under local anesthesia was performed. Histology of the surgical specimen confirmed the diagnosis of a true aneurysm measuring 8.4×5.7 mm, which showed no atherosclerotic degeneration of the vessel walls; the lumen was filled by a recent thrombus but without inflammatory cells. Surgical treatment is indicated for the prevention of rupture, the relief of pain when present, and the removal of facial defects. To the authors’ knowledge, this is the first case in the literature of a true aneurysm of the zygomatic orbital artery.